DYNAMIC MODEL SIMULATION OF SAGO RICE AVAILABILITY TO SUPPORT RESILIANCE CASE STUDY IN MERANTI ISLANDS DISTRICT - Harmaidi, Desma; Zargustin, Dedi; Putri, Vivin Jenika; Rahmah, Anania (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Sago is a typical Southeast Asian plant that is often found in water areas such as Meranti Regency. Even though Meranti Islands Regency in Sumatra is the largest center for sago growth, public consumption of sago is not yet in line with the high potential of this plant as a source of carbohydrates. In facing population growth and increasing food needs, sago has become a strategic commodity to maintain food security. This research uses dynamic modeling with Powersim Studio 7 to simulate planning scenarios to ensure the availability of sago in the future. Simulations show that Meranti Islands Regency can achieve the target of sago plantation area in 2032 with an accelerated growth policy, producing 3,915,168.71 tons of sago rice in 2040 and 499,182.72 tons in 2022.